Understanding gerontological nursing competence among nursing students in higher vocational colleges: a cross-sectional study - Chen, Qiu; Wang, Ke; Gao, Ying; Shen, Jun; Jia, QianYing; Wang, XinXia (Frontiers in Public Health, 2025)
BackgroundIn light of the global aging trend, society requires an adequate supply of nursing personnel to deliver care services to older people. Concurrently, nursing staff involved in older people’s care must possess sufficient theoretical knowledge, practical skills, and professional competence, which are critical determinants of nursing quality.Aims and hypothesesTo investigate the level of gerontological nursing competence among nursing students in higher vocational colleges and identify factors associated with it. Specifically, we hypothesize that nursing students with more gerontological nursing education and positive interaction experiences with older people will demonstrate higher levels of competence in gerontological nursing.MethodsA descriptive cross-sectional study was conducted from April to July 2024, including nursing students from two higher vocational colleges in Chongqing, China.Results1825 questionnaires were issued, and 1777 valid questionnaires were collected, with an effective recovery rate of 97.37%, and the total score of 1777 nursing students is (111.84 ± 23.01), which suggests that the overall gerontological nursing competence of nursing students is at the upper-middle level. Linear regression analysis revealed that grade, gender, being an only child at home, the relationship with grandparents, involvement in geriatric-related activities, prior experience in gerontological nursing education, and interest in gerontological nursing significantly positively influenced the competence of nursing students (p < 0.05).ConclusionThe majority of nursing students showed moderate to high levels of competence in gerontological nursing, which is essential for forming positive attitudes toward gerontological nursing. Statistical analysis revealed that gerontological nursing competence ratings were higher among nursing students who had received education in gerontological nursing, engaged in gerontological nursing practice, maintained positive social relationships with their grandparents, and exhibited an interest in gerontological nursing. This indicates that achieving a high degree of competency in gerontological nursing requires extensive theoretical knowledge, advanced understanding of gerontological nursing research, and a recognition of aging culture.